mHealth : transforming healthcare - Malvey, Donna (Springer US, 2014)
This book defines the phenomenon of mHealth and its evolution, explaining why an understanding of mHealth is critical for decision makers, entrepreneurs, and policy analysts who are pivotal to developing products that meet the collaborative health information needs of consumers and providers in a competitive and rapidly-changing environment. The book examines trends in mHealth and discusses how mHealth technologies offer opportunities for innovators and entrepreneurs, those who often are industry first-movers with regard to technology advancement. It also explores the changing dynamics and relationships among physicians, patients, insurers, regulators, managers, administrators, caregivers, and others involved in the delivery of health services. The primary focus is on the ways in which mHealth technologies are revising and reshaping healthcare delivery systems in the United States and globally, and how those changes are expected to change the ways in which the business of healthcare is conducted. mHealth: Transforming Healthcare consists of nine chapters that addresses key content areas, including history (to the extent that dynamic technologies have a history), projection of immediate evolution, and consistent issues associated with health technology, such as security and information privacy, and government and industry regulation. A major point of discussion addressed is whether mHealth is a transient group of products and a passing patient encounter approach, or if it is the way much of our health care will be delivered in future years with incremental evolution to achieve sustainable innovation of health technologies.